PENGEMBANGAN MEDIA PEMBELAJARAN CNC BERBASIS PERANGKAT LUNAK ANIMASI - Dwi Kusuma Ulinnuha; Budi Harjanto; Indah Widiastuti (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2019)
This research aims to (1) develop an instructional material based animation software for CNC course, (2) evaluate instructional material for CNC course that has been developed. The research was conducted at the Department of Mechanical Engineering Education, Faculty of Teacher Training and Education, Sebelas Maret University Surakarta. This research used Multimedia Development Life Cycle (MDLC) as research procedure, which consists of six stages, concept, design, collecting material, assembly, testing and distribution. Evaluation of instructional material for CNC course was performed by ask potential users to operate CNC instructional material that have been developed, then get response from potential users through a questionnaire. Potential users are divided into two categories, lecturers of CNC and CAM courses and students of Mechanical Engineering Education who take CNC and CAM courses in the academic year 2015/2016. Questionnaire for lecturers of CNC and CAM course reviewing instructional material from aspects of learning content, interaction, and presentation of the material. The questionnaire was given to 3 lecturers consisting of 15 point statements with Rating Scale as assessment system on intervals 1-5. Questionnaire for student reviewing instructional material from aspect of learning motivation as one of instructional material function. Questionnaire was given to 26 students consisting of 20 point statements with Likert Scale as assessment system on intervals1-5. The results of the research show (1) the development of instructional material for CNC course used Adobe Flash CS6 as main software with MDLC as development procedure, (2) the evaluation results show the instructional material for CNC course that developed gets (a) in aspects of learning content, interaction, and presentation of the material, the instructional material for CNC course gets very good category with percentage 90,22%, (b) in the aspect of learning motivation as one of instructional material function, the instructional material for CNC course gets good categories with percentage 78,39%.